The development of lived experience-centered word clouds to support research uncertainty gathering in degenerative cervical myelopathy: results from an engagement process and protocol for their evaluation, via a nested randomized controlled trial. - Davies, Benjamin M; Mowforth, Oliver D; Khan, Danyal Z; Yang, Xiaoyu; Stacpoole, Sybil R L; Hazenbiller, Olesja; Gronlund, Toto; Tetreault, Lindsay; Kalsi-Ryan, Sukhvinder; Starkey, Michelle L; Sadler, Iwan; Sarewitz, Ellen; et al. (Apollo - University of Cambridge Repository, 2021)
Objectives
AO Spine REsearch objectives and Common Data Elements for Degenerative Cervical Myelopathy [RECODE-DCM] is a multi-stakeholder consensus process aiming to promote research efficiency in DCM. It aims to establish the top 10 research uncertainties, through a James Lind Alliance Priority Setting Partnership [PSP]. Through a consensus process, research questions are generated and ranked. The inclusion of people with cervical myelopathy [PwCM] is central to the process. We hypothesized that presenting PwCM experience through word cloud generation would stimulate other key stakeholders to generate research questions better aligned with PwCM needs. This protocol outlines our plans to evaluate this as a nested methodological study within our PSP.
Methods
An online poll asked PwCM to submit and vote on words associated with aspects of DCM. After review, a refined word list was re-polled for voting and word submission. Word clouds were generated and an implementation plan for AO Spine RECODE-DCM PSP surveys was subsequently developed.
Results
Seventy-nine terms were submitted after the first poll. Eighty-seven refined words were then re-polled (which added a further 39 words). Four word clouds were generated under the categories of diagnosis, management, long-term effects, and other. A 1:1 block randomization protocol to assess word cloud impact on the number and relevance of PSP research questions was generated.
Conclusions
We have shown it is feasible to work with PwCM to generate a tool for the AO Spine RECODE-DCM nested methodological study. Once the survey stage is completed, we will be able to evaluate the impact of the word clouds. Further research will be needed to assess the value of any impact in terms of stimulating a more creative research agenda.
Keywords: Surveillance; Cervical; Protocol; Research priorities; Spondylosis; Audit; Myelopathy; Disc Herniation; Outcome; Consensus; Opll; Delphi; Dataset; Cervical Stenosis; Word Cloud; Common Data Elements (Cde); Core Outcomes In Effectiveness Trials (Comet); James Lind Alliance (Jla); Humans; Spinal Cord Diseases; Uncertainty; Health Priorities; Randomized Controlled Trials as Topic; Surveys and Questionnaires